Aplikasi Bioteknologi pada Tanaman sebagai Alternatif Pencegahan Krisis Pangan - Rahmawati, Aulia; Fitrianingsih, Dewi (Agritechpedia, 2023)
Agricultural biotechnology is a new tool for improving plants and animals. This technology uses cell DNA combination/synthesis technology to improve plants and animals or create new products. Biotechnology plant products approved for food have the following properties: 1) resistance to pests and diseases, 2) resistance to herbicides, 3) changes in diet, and 4) increased resource-conserving concentrations. Rapid population growth is currently a major challenge for the food industry. After rice and corn, soybeans are an important commodity. This species is considered an important protein source and raw material for various food and feed industries. The need for some products cannot be fulfilled domestically, so they have to be imported. To overcome these problems, technological readiness (creation of tolerant superior varieties and use of biological fertilizers) and the promotion of cultivation technology to increase productivity towards self-sufficiency are very reasonable. The purpose of compiling this journal is to provide information about improving the quality of crop production through the use of biotechnology in overcoming food scarcity. Plants that are almost experiencing scarcity are carried out by efforts to preserve germplasm. Biotechnology is an alternative genetic engineering technology that is able to overcome the problem of food crisis by increasing crop productivity.Keywords: Biotechnology, Soybean, Food, Superior varieties